Theocritus and Things Material Agency in the Idylls - Canevaro, Lilah (Ancient Cultures, New Materialisms, 2023)
This book contributes to the literary-theoretical field of Material Ecocriticism, expanding its chronological remit, and is the first to apply it to Classics. Material Ecocriticism has been described as an exercise in listening - and it is to a series of underrepresented agents (women, nature, the nonhuman) in the poetry of Theocritus that this book urges us to listen. This 'from below' reading that allows nature and materiality their agency, that sees objects and the labour behind them, gives a new way in to the paradoxes of Hellenistic pastoral poetry: the urban backdrop to bucolic poetry, the artifice of the locus amoenus. This book reveals a detailed picture of material agency and a diverse cast of characters human and nonhuman in Theocritus' Idylls, showing that while the poetry might be paradoxical it is not rarefied. And through a dark-ecological reading it highlights the darkness that undercuts the idyll.